Unity Game Development Scripting : write efficient C♯ scripts to create modular key game elements that are usable for any kind of Unity project /: write efficient C♯ scripts to create modular key game elements that are usable for any kind of Unity project. (2014) - D'Aoust, Kyle
No abstract available